CASE REPORT: POSTINFECTIOUS BROWN SÉQUARD PLUS SYNDROME - Dilek Karakuş; Canan Çelik; Nesrin Yaraman; Belgin Karaoğlan; Hilmi Uysal (Archives of Rheumatology, 2005)
In this case report we present a 17 year old female patient who has developed postinfectious tetraplegia. It was diagnosed as an atypical form of myelitis which was called Brown Sequard Plus Syndrome (BSPS). BSPS is rare but has better prognosis than other myelitis form.